Studies on correlations between urine parameters and flux variations on human urine using He-Ne laser and encircled flux analy - Nizam Alias, Azrul (2007)
In this research, correlations between urine parameters is studied by finding patterns and statistical tests using SigmaStat 3.1 and flux variations using 0.95 mW He-Ne laser and Encircled Flux Analysis System (EFAS). Data obtained from statistical analysis shows correlations and consistencies with other researchers. These consistency are reflected from the correlations obtained between urine pH, age, urine specific gravity, urine protein and urine glucose. Conversely, the inconsistencies of the results are shown between urine specific gravity and age and also between urine specific gravity and urine protein. The studies on urine parameters by flux variations exhibits significant patterns. Flux peak and total flux for males show increasing pattern for urine pH and specific gravity while for females show decreasing pattern. Flux peak for males and total flux for females shows increasing pattern when aging while total flux for males and flux peak for females shows decreasing pattern. The pattern of 2D contour and 3D profile gives individual pattern according to gender, urine health and age groups. This research shows that using He-Ne laser and EFAS exhibited a good future prospect in urine research. Flux parameters such as flux peak and total flux, can become significant parameters for analysts of urine.